Розробка високоефективної технології отримання біогазу - Стародуб, Н. Ф.; Шворов, С. А.; Комарчук, Д. С.; Лукін, В. Є.; Устимчук, В. В. (Energy and Automation, 2017)
DEVELOPMENT HIGH EFFECTIVE TECHNOLOGIES OF BIOGAS PRODUCTIONN. Starodub, S. Shvorov, D. Komarchuk, V. Lukin. V. Ustymchuk One of the important sectors of renewable energy in the world is producing and using biogas energy. In addition, the full and rapid implementation of biogas technologies for the processing of both plant and animal radically improve the energy balance of the country and state environmental areas.Analysis of recent research and publications shows that fixed dosage of input substrates is determined at the stage of construction of biogas plants. In the process established not expected BSU use in different types of seasonal biomass. This sub-optimal process control loading different types of substrates can significantly reduce the release of biogas. One promising avenue eliminate these shortcomings is the development of biogas technology, through which the load is provided BSU different types of input substrates and special additives and create the necessary conditions for the maximum possible amount of biogas.The aim - to develop highly innovative biogas technology for the preparation of input substrates and optimal dosing of special additives to obtain the maximum volume of biogas.One of the areas of intensification of fermentation is the optimal dosage and destruktsiyna (cavitation) processing of various raw materials, optimum heating and mixing with the required intensity loaded substrate, providing efficient use of the entire volume of the tank BSU, prevents the formation of "dead" zones, separation of sludge, laying mineralized sediment and crust formation, and also helps equalize the temperature field and the improvement of gas.Fermentation process intensification is that the flow of various raw materials in the rotary pulsation apparatus BSU microscopic crushed to the required level and homogenized. During treatment torn ligament long fibers (lignin, cellulose). Dispersion increases so that the particles are reduced in size to 0.1 microns. Because the bacteria involved in the formation of biogas biogenic materials decompose easily. As a result, methane content in biogas is increased to 70-75 %.Using a special immune biosensor is determined by the number and rate of growth of microbial populations in fermented biomass necessary for optimal dosing of various types of special additives, which can significantly increase the yield of biogas. When impurities in this case refers to a mixture of enzymes, trace elements, etc., the use of which provides increased biogas output from 20 to 40% without changing the design of the biogas plant. In biogas plants in Germany impurities of this type provide guaranteed biogas yield of 45%. The estimated their value is about 42 EUR / kg at the rate of 1-2 kg per day for biogas power station with a capacity of 1 MW.The basis of biogas technology is a highly efficient management system BSU whereby based on an analysis of data provided by dosing biosensor various raw materials, grinding it to the desired microscopic level and optimal dosage special additives.As the results of theoretical and practical research, the largest output biomethane provide substrates with a high concentration of energy, fresh grass, beet tops, corn, cereal plants. The lowest yield of biogas from organic substrate is dry straw.With the proposed biogas technology provided the following key terms of biogas production.Bacteria can actively work only in the absence of oxygen, ie under anaerobic conditions. The production of biogas is carried out in a wet environment, because only under these conditions bacteria can function. The best mode for all groups of bacteria is a temperature range of 35-40 °C, which also provides biogas technology with the projected temperature. During fermentation the amount of gas produced gradually increases corresponding increase in its duration, and at first it is faster, and with increasing duration of fermentation - slowly. Hydrolysis and acid-bacteria in the environment with a level of optimum pH 4,5-6,3 reach their activity, while bacteria that form acetic acid and methane can live only at neutral or slightly alkaline at the level of pH 6,8-8. For all bacteria are generally valid if the pH exceeds the optimum, they become less active in his life, delaying the formation of biogas.Qualitative mixing of substrates is important not only to avoid the appearance of crust and sediment, but also to biogas was removed to the surface.Using a special optical immune biosensor based on surface plasmon resonance is determined by the amount and rate of growth of microbial populations in fermented biomass necessary for optimal dosing of various types of EC and special additives, which together with the cavitation destructors biomass can significantly increase the biogas yield for different species energy.On the basis of highly innovative biogas technology provided:implementation of the required degree of grinding and homogenisation of raw materials intensifies the production of biogas;reducing biomass digestion period due to the high dispersion intensification of biomass and anaerobic digestion;saving costs for construction and operation of BSU;intense release natural enzymes that are biological catalysts biomass fermentation process, which also increases the amount of produced biogas;stabilization of the temperature and biological processes for biomass degradation of cellular and subcellular material that prevents foaming and crust floating on top of the bioreactor. Thus, all the useful volume of the reactor is used effectively. The percentage of methane in biogas is increased to 70-75 %.